107k views
4 votes
2(3x – 4)= -2(x - 2

User Fat Monk
by
5.1k points

2 Answers

4 votes

Answer:

2(3x-4)=-2(x-2)

6x-8=-2x+4

6x+2x=4+8

8x=12

x=12/8

x=3/2 or x=1.5

User Eucalculia
by
5.8k points
4 votes


\huge \pink \star{ \green{ \boxed{ \boxed{ \boxed{ \purple{ \mathfrak{Answer: }}}}}}} \pink\star⋆

2(3x – 4)= -2(x - 2)

6x - 8 = -2x + 4

6x + 2x = 4 + 8

(After shifting the terms from LHS to RHS or RHS to LHS, the negative terms become positive and positive terms become negative)

8x = 12

x = 12/8 (÷ by 2)

x = 3/2


\mathfrak\purple {Hope\: this\: helps\: you...}

User Darmis
by
5.0k points